FAKTOR FAKTOR YANG MEMPENGARUHI KEAKTIFAN PASIEN PROGRAM PENGELOLAAN PENYAKIT KRONIS DI PUSKESMAS KIANGROKE KABUPATEN BANDUNG - Hariany, Mery; Hariningsih, Wintari; Juliyanti, Juliyanti (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2025)
The Chronic Disease Management Program (Prolanis) aims to improve patients' quality of life through a promotive and preventive approach. However, patient engagement in this program is influenced by various factors, such as knowledge, individual attitudes, family support, and healthcare worker support. This study employed a quantitative method with a cross-sectional design involving 65 Prolanis participants, where data were collected through questionnaires and analyzed using bivariate tests. The majority of respondents were female (76.9%) with a low educational level (78.5%), low knowledge (78.5%), positive attitudes (80%), family support (78.5%), and healthcare worker support (84.6%). Patient engagement in Prolanis reached 89.2%. Bivariate analysis showed that knowledge level was not significantly related to patient engagement (p-value 0.142). In contrast, individual attitudes (p-value 0.009), family support (p-value 0.001), and healthcare worker support (p-value 0.001) were significantly associated with patient engagement in Prolanis. The study concludes that family and healthcare worker support are the main factors in enhancing patient engagement in Prolanis. Therefore, interventions focused on increasing social support and strengthening patients' positive attitudes are essential to improve participation and the effectiveness of this program.